The role of the structural fibrosis markers in the left atrial remodeling in patients with paroxymal atrial fibrillation - A. I. Gozhenko; E. M. Levchenko; A. V. Goriachyi; V. I. Kushnirenko (Kazimierz Wielki University, 2017)
In a study the indicators of cardiac fibrosis at patients with paroxysmal form of atrial fibrillation were investigated. The study group consisted of patients with paroxysmal atrial fibrillation in combination with hypertension and without it. Signs of the left atrium dilation have been identified in comparison to healthy patients. At the same time smaller changes were observed in patients with atrial fibrillation without hypertension. Whereas in the group of patients with arterial hypertension signs of dilatation of the left atrium were most significant. In the study of correlations with indicators of fibrosis echocardiographic parameters found that significant associations observed mainly in index PICP with the parameters of the left atrium. The increase in size of the left atrium PICP associated with increasing concentrations of TIMP-1 and MMP-9.